2013
DOI: 10.1016/j.rehab.2013.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient cardiac rehabilitation and changes in self-reported health related quality of life – a pilot study

Abstract: These findings indicate an improvement in HRQoL over time among cardiac patients attending the rehabilitation programme, particularly so in the domains of physical role and physical function, vitality, bodily pain and emotional-, physical- and social-well-being, all which are important domains for maintaining an active life. Future randomised studies comparing inpatient- and outpatient-programmes with longer follow-up are necessary to ascertain if such improvements persist and if patients are able to change li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…After the CABG surgery, there was an improvement in general health (GH), which may be related to the reduction or elimination of angina and chest pain [28], which is consistent with the results of this study. After rehabilitation, a significant improvement in all domains of quality of life was observed in our patients, and the highest score was recorded in the pain scale, which is consistent with other research findings [39,40]. Quality of life has been found to deteriorate shortly after the intervention and then moves in a positive direction with patient recovery within a year [41].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…After the CABG surgery, there was an improvement in general health (GH), which may be related to the reduction or elimination of angina and chest pain [28], which is consistent with the results of this study. After rehabilitation, a significant improvement in all domains of quality of life was observed in our patients, and the highest score was recorded in the pain scale, which is consistent with other research findings [39,40]. Quality of life has been found to deteriorate shortly after the intervention and then moves in a positive direction with patient recovery within a year [41].…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study showed an improvement in general health status after surgery and after rehabilitation in these patients, which is consistent with other studies [10,18,[26][27][28]34,39,50]. However, although there has been an improvement in quality of life 1 year since surgery, the results indicate an unsatisfactory quality of life for patients after CABG surgery.…”
Section: Discussionsupporting
confidence: 91%
“…Overall, the results showed that health promotion programs after CABG can reduce the risk factors of the disease in patients. Evidence suggested it is better to begin education programs while the patient is in hospital still ( Weberg et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing prevalence of CAD reflects the effects of the many risk factors that are becoming more common such as type 2 diabetes mellitus, obesity, sedentary lifestyle, stress and fatty diet ( Mozaffarian, Wilson, & Kannel, 2008 ). Clinical evidences demonstrated that a sedentary lifestyle, stress and fatty diet are significant modifiable risk factor for CHD ( Weberg, Hjermstad, Hilmarsen, & Oldervoll, 2013 ). Cardiac rehabilitation and HPPs are the most common form which they medically supervised exercise programs, stress management and diet that have been shown to improve health and decrease risk factors ( Koch, Li, Lauer, Sabik, Starr, & Blackstone, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a study evaluating post-CR quality of life of patients using SF-36, a significant improvement was observed in physical functioning, role limitations due to physical problems, emotional role, energy, social function and pain, with no difference in general health perception and mental health [31]. In another study using SF-36, a significant increase was identified in post-CR physical role, physical functioning, energy, pain and emotional, social, mental wellbeing [32]. In line with the said study, we found a significant improvement in physical role, physical functioning, mental health, social functioning and pain, which are SF-36 parameters, in the non-obese group.…”
Section: Discussionmentioning
confidence: 99%